Pengembangan Modul Pelatihan Pengelolaan Penilaian Autentik Guru IPA SMP - Vidriana Oktoviana Bano (Universitas Kristen Satya Wacana, 2018)
This research aims to: (1) describe the real condition of authentic assessment of management by science teachers at SMP Negeri 1 in Waingapu; (2) describes the gaps that occur in the management of authentic assessment; and (3) develop training modules in the management of authentic assessments. This Research is Research and Development (R & D), using the Four D’s model by Thiagarajan, Semmel, and Semmel (1974). Data collection uses interview, questionnaire, observation. Data validation uses source triangulation and technical triangulation. Data analysis techniques through three stages are data reduction, presentation, and conclusion. The results explain (1) teachers of science limited constraints in practicing the attitude and skill assessment of the learners. (2) limited training of Curriculum 2013 especially authentic assessment that has been followed by trainees. (3) the validator team puts the effectiveness of the training module for the management of authentic assessment of science teachers in junior high school in the fair category with a score of 102 out of 150 or 68%. After improving the module and tested it, the training participants' response was 79.75% in the good category and the educational observers' response was 78,4% with the good category as well.